Self-Management Training to Reduce Employee Stress Levels - Meliasari Anggraeni; Amalia Muthmainnah Lundeto; Putrawansyah Putrawansyah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Cleaning service workers, as outsourced employees, play a crucial role in maintaining workplace hygiene and comfort but often face psychological strain due to heavy workloads, monotonous routines, and inequitable reward systems. This study applied a psychological intervention approach based on the Job Demand-Resources (JD-R) theory, beginning with initial assessments to identify stress levels and contributing factors. A structured stress management training program was then conducted in group sessions, focusing on stress understanding, symptom recognition, and adaptive coping strategies. Assessments and interventions revealed that most workers experienced occupational stress consistent with the JD-R theory, which explains that stress arises when job demands exceed available resources. To address this issue, the training emphasized breathing relaxation, cognitive restructuring, and time management. Evaluation results demonstrated significant improvements in participants’ emotional regulation and coping skills, enabling them to manage work pressure more effectively. The intervention proved beneficial in reducing stress levels and enhancing psychological well-being, suggesting that stress management training should be adopted as a sustainable initiative to strengthen human resource quality in outsourced work environments.